Interprofesional Colaboration Practice terhadap Kepuasan Kinerja Perawat: Kajian Literatur - Sembiring, Nur Maghribi; Sembiring, Muhammad Simba; Sembiring, Sisi Maghfirah Rahmah (Fakultas Ilmu-ilmu Kesehatan Universitas Jenderal Soedirman, 2024)
Background: This is in accordance with findings from World Health Organization (2021), that poor communication and understanding within the team is approximately 70 - 80% errors in health services are caused by the phenomenon of poor communication in Indonesia and in the world. medical errors reached 4.1% - 91.6%. This is caused by an error 54% of prescriptions were given errorsdrug administration as much as 11%, and drug use incorrect as much as 46%. Interprofessional collaboration is partnerships between professions with backgrounds different education and work together to solve patient health problems as well provide needed health services. Aim: For know what an Interprofessional looks like Collaboration on Nurse Performance Satisfaction in world and in Indonesia through reviews from various literature. Methods: This study uses a literature review design. The data used were taken from four databases, Google Scholar, SinceDirect, Proquest, PubMed. and were searched based on specified inclusion and exclusion criteria. Article search results is presented in the PRISMA diagram. The articles obtained are then performed Critical Appraisal and due diligence using Joanna Briggs Institute (JBI) tools, then analysed using the simplified thematic approach. Result: The search results obtained as many as 1.102 articles from the four databases. The search limit was in the form of Indonesian and English articles from 2018-2023. and a total of ten articles were researched. Conclusion: There are seven derivatives with several subtitles that the author has created explained among them are Interprofessional collaboration between nurses and doctors, Nurse satisfaction with interprofessional team members, Nurse-Doctor Collaboration, Moral Pressure, and Professional Autonomy to Satisfaction Nurses work as assistants. Implementation of nurse-doctor collaboration in inpatient rooms after the Covid-19 pandemic. Implementing interprofessional collaboration practice in improving nurse performance, interprofessional collaboration and nurse burnout. and the last one is the speak up method to improve interprofessional.